Pattern of Kidney Stress Symptoms and Associated Factors among Outdoor Workers in Port Harcourt, Rivers State - Tamunobelema T.I; Emem-Chioma P.C; David-West M; Zaccheaus M; Achi-Kalu E; Okwuosi M; Enwurum J; Nkangwu D; Idoma E; Allison F.I (International Journal of Health & Medical Research, 2026)
Background: Outdoor workers experience prolonged exposure to heat, solar radiation and strenuous physical activity, which may promote dehydration and kidney stress. This study assessed self-reported kidney stress symptoms and associated factors among outdoor workers in Port Harcourt, Nigeria. Methods: A descriptive cross-sectional study was conducted among 150 outdoor workers. Data were collected using a structured interviewer-administered questionnaire covering socio-demographic characteristics, outdoor work exposure, hydration practices and kidney stress symptoms. Symptoms assessed included dark urine, oliguria, dysuria, flank or back pain and leg or stomach cramps. Data were analysed using descriptive statistics and chi-square tests in SPSS. Statistical significance was set at p